The Social Status Of Female Characters In Chi Li’s Novels 池莉小说中女性的社会地位 - Mariana Mariana (Lingua Cultura, 2012)
Chi Li is a novelist writing “new realism” novels based on the custom of Wu Han people. Chi Li’s works have different social background according to different period stages. The first period of her works was at early 80s called beginner period. The second period was at mid 80s until mid 90s called famous period. The last period was at the end of 90s until now called evolution period. Chi Li created different female characters on different work stages. At the first period, Chi Li described the females were still obedient to the tradition. Their self-determination consciousness was weak and depended to men. At the second period, Chi Li’s female characters were changed into awaken ones who sought a new way of life. They could survive and make life by themselves, but the traditional concepts still influenced their thoughts. They still believed that devotion to men was the life idealism.Meanwhile, strong personality, strong self-determination consciousness, independence were female characters found in Chi Li’s last period works.